SPIKE1 Activates ROP GTPase to Modulate Petal Growth and Shape. Issue 1 (20th July 2016) - Ren, Huibo; Dang, Xie; Yang, Yanqiu; Huang, Dingquan; Liu, Mengting; Gao, Xiaowei; Lin, Deshu
Abstract : SPIKE1 activates ROP GTPase proteins to regulate anisotropic cell expansion and petal anisotropic growth by affecting the organization of cortical microtubule arrays in Arabidopsis. Abstract: Plant organ growth and final shape rely on cell proliferation and, particularly, on cell expansion that largely determines the visible growth of plant organs. Arabidopsis ( Arabidopsis thaliana ) petals serve as an excellent model for dissecting the coordinated regulation of patterns of cell expansion and organ growth, but the molecular signaling mechanisms underlying this regulation remain largely unknown. Here, we demonstrate that during the late petal development stages, SPIKE1 (SPK1), encoding a guanine nucleotide exchange factor, activates Rho of Plants (ROP) GTPase proteins (ROP2, ROP4, and ROP6) to affect anisotropic expansion of epidermal cells in both petal blades and claws, thereby affecting anisotropic growth of the petal and the final characteristic organ shape. The petals of SPK1 knockdown mutants were significantly longer but narrower than those of the wild type, associated with increased anisotropic expansion of epidermal cells at late development stages. In addition, ROP2, ROP4, and ROP6 are activated by SPK1 to promote the isotropic organization of cortical microtubule arrays and thus inhibit anisotropic growth in the petal. Both knockdown of SPK1 and multiple rop mutants caused highly ordered cortical microtubule arrays that were transversely oriented relative to the axis of cell elongation after development stage 11. Taken together, our results suggest a SPK1-ROP-dependent signaling module that influences anisotropic growth in the petal and defines the final organ shape.